2015
DOI: 10.1111/jpy.12325
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in macroalgae: advances and future perspectives

Abstract: Polyamines (PA) are ubiquitous, small, aliphatic cations found in all living cells. In recent years the importance of these molecules for macroalgae has become evident and a substantial body of knowledge has been accumulated over the last three decades. This review summarizes research on the PAs found in macroalgae, their transport and metabolism, and their biological significance in processes such as cell division, chloroplast development, and reproduction. The involvement of PAs in environmental stress respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 139 publications
(292 reference statements)
0
7
0
Order By: Relevance
“…However, despite intensive research, their role and mechanism of action in algae and higher plants are still poorly understood. Modulation of their levels influences growth, cell division, metabolite profiles, transcriptome patterns, responses to stressors (e.g., salinity and oxidative stress), and other physiological functions [21,[47][48][49][50][51][52][53][54][55][56][57][58]. In synchronized C. reinhardtii cultures, transition to the cell division phase was preceded by a 4-fold increase in ornithine decarboxylase activity and a 10-fold increase in putrescine level.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite intensive research, their role and mechanism of action in algae and higher plants are still poorly understood. Modulation of their levels influences growth, cell division, metabolite profiles, transcriptome patterns, responses to stressors (e.g., salinity and oxidative stress), and other physiological functions [21,[47][48][49][50][51][52][53][54][55][56][57][58]. In synchronized C. reinhardtii cultures, transition to the cell division phase was preceded by a 4-fold increase in ornithine decarboxylase activity and a 10-fold increase in putrescine level.…”
Section: Discussionmentioning
confidence: 99%
“…Selected reviews focus on the essential roles of polyamines, polyamines in secondary metabolism as well as polyamine alkaloids and conjugates. 807–824…”
Section: The Isolation Of Water-soluble Natural Productsmentioning
confidence: 99%
“…Numerous studies in plants and macroalgae have shown that polyamines play important roles in protecting against abiotic stresses [10,145,146,147,148,149]. Like many autotroph organisms, microalgae must to cope with environmental stress in nature, such as a lack of nutrients, temperature fluctuations, and excessive light.…”
Section: The Physiological Roles Of Polyamines In Microalgaementioning
confidence: 99%